The use of ion-exchange resins for the recovery of valuable species from slurries of sparingly soluble solids - De Villiers, Pieter Gabriel Retief (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2002.